2020
DOI: 10.1093/hmg/ddaa272
|View full text |Cite
|
Sign up to set email alerts
|

SNP-adjacent super enhancer network mediates enhanced osteogenic differentiation of MSCs in ankylosing spondylitis

Abstract: Ankylosing spondylitis (AS) is a rheumatic disease with pathological osteogenesis that causes bony ankylosis and even deformity over time. Mesenchymal stem cells (MSCs) are multipotent stem cells that are the main source of osteoblasts. We previously demonstrated that enhanced osteogenic differentiation of MSCs from AS patients (ASMSCs) is related to pathological osteogenesis in AS. However, the more concrete mechanism needs further exploration. Super enhancers (SEs) are dense clusters of stitched enhancers th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Sustained ER stress in AS bone-derived cells stimulates the activation of the RUNX2 and C/EBP-β genes ( Jo et al, 2017 ). Single-nucleotide polymorphism-adjacent super enhancers modulate the enhanced osteogenic differentiation of AS-BMSCs( Yu et al, 2021 ). However, the function of circRNAs in BMSCs of patients with AS is still unknown and research is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustained ER stress in AS bone-derived cells stimulates the activation of the RUNX2 and C/EBP-β genes ( Jo et al, 2017 ). Single-nucleotide polymorphism-adjacent super enhancers modulate the enhanced osteogenic differentiation of AS-BMSCs( Yu et al, 2021 ). However, the function of circRNAs in BMSCs of patients with AS is still unknown and research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…When new bone forms in the sacroiliac joint, spine and the hip joint, the AS patients generally become ankylosed. Our previous studies documented that long noncoding RNAs and super enhancers are involved in the pathogenesis of osteogenesis in AS ( Xie et al, 2016a ; Yu et al, 2021 ). However, the mechanism of pathological osteogenesis needs to be further elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The cck8 assay was performed according to the protocol provided by the manufacturer [ 53 ]. Briefly, 2,000 cells were plated in a 96-well tissue culture plate for 8 h and then co-cultured with 8 000 (1:4) CD3 + T cells.…”
Section: Methodsmentioning
confidence: 99%
“…Considering osteogenic differentiation, Yu et al. ( 28 ) have reported that the single-nucleotide polymorphisms (SNP)-unique ankylosing spondylitis (AS) SNP-adjacent SEs (SASEs)-mRNA network participated in the pathological osteogenesis of AS and enhanced the osteogenic differentiation ability of MSCs from AS patients (ASMSCs). Overall, research regarding the role of SEs in bone-related diseases and osteogenic differentiation has mainly focused on SEs-associated mRNAs but few studies have addressed SEs-associated lncRNAs.…”
Section: Introductionmentioning
confidence: 99%